2002
DOI: 10.1016/s0736-5748(02)00038-2
|View full text |Cite
|
Sign up to set email alerts
|

Getting the point: electrophysiological correlates of protodeclarative pointing

Abstract: We examined the longitudinal relationships between power data in two bands (i.e. 4-6 and 6-9Hz) of electrical activity in the brain at 14 months, as measured by background electroencephalograms (EEG), with protodeclarative and protoimperative pointing at 18 months, as measured by the Early Social Communication Scales (ESCS), [Mundy et al., ESCS: A Preliminary Manual for the Abridged Early Social Communication Scales, 1996, unpublished manual] (n=27). EEGs were recorded from 64 sensors using the Electrical Geod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 39 publications
6
58
1
2
Order By: Relevance
“…The locus of this effect modulating the readiness potential is reminiscent of a previous study investigating pointing by infants, which also identified a frontocentral marker of communicative intent measured using EEG (Henderson et al, 2002). Several other studies have also linked frontal effects in ERPs to "mentalizing" or theory-of-mind-related activations (e.g., Liu, Sabbagh, Gehring, & Wellman, 2004;Sabbagh, 2004) and recent neuroimaging studies relate activity in neuronal structures in frontal cortex to the mentalizing involved in the production and comprehension of communicative pointing (e.g., Brunetti et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The locus of this effect modulating the readiness potential is reminiscent of a previous study investigating pointing by infants, which also identified a frontocentral marker of communicative intent measured using EEG (Henderson et al, 2002). Several other studies have also linked frontal effects in ERPs to "mentalizing" or theory-of-mind-related activations (e.g., Liu, Sabbagh, Gehring, & Wellman, 2004;Sabbagh, 2004) and recent neuroimaging studies relate activity in neuronal structures in frontal cortex to the mentalizing involved in the production and comprehension of communicative pointing (e.g., Brunetti et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…A subset of five ROIs was selected for the analyses (see Figure 3) based on previous, related work outlined in the Introduction. An anterior ROI was selected on the basis of the findings in Henderson et al (2002). A potential modulation of the readiness potential as a function of our informativeness manipulation would be reflected in an effect over left central but not right central electrode sites, because all participants were right-handed and pointing with their right index finger.…”
Section: Electrophysiological Recording and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a longitudinal study of EEG coherence in infants from 14 to 18 months of age described EEG data suggesting left frontal and left and right central activation was associated with IJA ability at 14 and 18 months (Mundy et al, 2000). This finding was expanded upon by Henderson et al (2002) who used dense array electrodes for their EEG recordings and found medial frontal cortical activation in both hemispheres was associated with better IJA performance. The authors also report that activation of orbitofrontal, temporal and dorsolateral cortex was related to IJA.…”
Section: Infant Electrophysiological and Functional Neuroimaging Studiesmentioning
confidence: 98%